Karya Tari Sky Maps - Swarsana, I Putu; Suandewi, Gusti Ayu Ketut; Kasih, Ni Nyoman (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2024)
Sky Maps is a contemporary dance work inspired by constellations. A constellation is a collection of stars connected into a pattern in the sky. In addition to predicting luck, the uses of constellations include, among others, as a sign for planting time, and also used as navigation or directions for fishermen at sea. Constellations can also be used to determine the cardinal directions in each direction east, south, west, north have their own constellations. The constellations consist of the Scorpio constellation, the Kite constellation, the hunter constellation, and the thunder constellation. This work focuses on the shape of each constellation transformed into dance movements according to the imagination of the stylist with his creativity. The process of creating Sky Maps uses the method of Alma M. Hawkins in her book Creating Through Dance translated by Y. Sumandiyo Hadi into the book Creating Through Dance, which mentions three important stages in the formation of dance works, namely, the exploration stage, the experimental stage (improvisation), and the forming stage. The Sky Maps dance work is danced by eight male dancers who are packaged into a contemporary dance form with a duration of approximately 14 minutes. The Sky Maps dance work uses MIDI (Musical Instrument Digital Interface) music in which there are several electronic music instruments to support the atmosphere in this dance work. This work uses fantasy makeup with clothing that uses a white jumpsuit (strait full body) with a combination of navy blue and uses reflective strips (scothlite) which are arranged in such a way in one dancer's outfit. The effect of the reflector strip (scothlite) itself reflects light when illuminated and will emit light when in the dark. Besides having a uniqueness that lies in the idea and concept, another uniqueness also lies in the movement called Nyiku Lintang.